Reverse zoonotic transmission of human seasonal influenza to a pig herd in Sweden - Sylvén, Kaisa Ryytty; Jacobson, Magdalena; Schwarz, Lukas; Zohari, Siamak (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2024)
In January 2023, a Swedish piglet-producing farm with 2800 sows in production (SIP) was diagnosed with IAV (Influenza A virus) and the isolates were shown to cluster with the human seasonal influenza (2022/2023). In December 2022, employees with flu like symptoms tended to the pigs and a few weeks later, respiratory signs appeared in different age groups; sows in farrowing units were anorectic and pyrectic. Lung and nasal swabs were tested positive for IAV and other respiratory infectious agents. Blanket vaccination against H1N1pdm09 of sows and gilts was initiated but discontinued for sows after 2 treatments. Biosecurity measures aiming to reduce the spread of virus were implemented. However, the compliance to follow the protocol was moderate.Combining immunity and strict sanitary measures is crucial to control virus circulation. As the farmer discontinued sow vaccination and just partly increased biosecurity, this may have contributed to ongoing virus circulation and clinical signs in pigs, even 5 months post-diagnosis. Although H1N1pdm09 already had been found in the herd in 2017, there were no clinical signs or diagnostic results indicating continuous circulation of this or other IAV strains afterwards. However, this cannot be entirely excluded. Swine IAVs pose a risk of reintroduction into the human population, highlighting the importance of vaccination of farm workers against seasonal influenza.
Keywords: Pig; Influenza A Virus; IAV; H1N1pdm09; NGS; reverse zoonotic